Principles of Auditing & Other Assurance Services - Whittington, O.Ray (MacGraw-Hill, 2014)
The 9th edition has been to reflect a number of events, to make the material more understandable, and to increase the scope of objective question coverage, including: - Clarity standards, Audit evidence, Group audits, Service organizations, Objective questions....